GIS based Model for Evaluating Effects of Agricultural EU Funds - Kranjac, Mirjana Vera; Stankov, Ugljesa; Salom, Jakob; Tomašević, Vladimir; Tomić, Srđan (Geographica Pannonica, 2019)
European Union (EU) is giving significant financial support to member states through Common agricultural policy (CAP). Problem is that effects of EU giving are often not well presented and their effects are not recognized. The goal of this paper is to present model of visualisation using geographic information systems as effective tool for fast analysis and application of immediate correction measures. Results gained by using GIS show that there is only 7.4% of EU countries with significant positive correlation between invested funds and agricultural outputs.